By accident or by design? Influence of government policies on drivers and barriers of smallholder teak growing in Lao PDR. Issue 1 (2nd January 2019) - Arvola, Anne; Anttila, Juho-Pekka; Hogarth, Nicholas
ABSTRACT: This study analyses the impact of policy, legal and market conditions and specific incentives on smallholders' interest and success in tree growing between 1990-2015 in Lao People's Democratic Republic (Laos, Lao PDR). A review of previous studies and policy papers established the framework for this study, with primary data then collected from smallholders through semi-structured interviews in four villages. The interview questions covered household socioeconomic features, land use, information on woodlots, extension, and perceptions on drivers and challenges of tree growing. The findings indicate that policy objectives of promoting smallholder tree growing are weak at the district and village levels, and the only significant incentive, namely land allocation, has become ineffectual due to land scarcity and preference for other income sources. Tree growers intend to mainly preserve their present plantation areas, although their interest to expand tree growing areas is weak, and one third of non-growers see tree growing as a potential livelihood diversification option. If the promotion of smallholder tree growing is to be improved, the land and forest policy and associated legislation requires thorough revision and simplification, extension services must be made available, and specific incentives developed to allow smallholders to access land and meet their specific needs.